Hydraulic performance of free surface breakwaters: a Review - H.M., Teh (Universiti Kebangsaan Malaysia, 2013)
This paper introduces the concept of free surface breakwaters for coastal protection. The advantages, limitations and applications of these breakwaters are discussed. Based on their configurations, free surface breakwaters have been classified into four types, namely solid-type, plate-type, caisson-type and multipart-type. Typical designs of the respective breakwater types are presented and the hydraulic characteristics are reviewed. In addition, comparisons of hydraulic efficiency of some of the free surface breakwaters are also addressed in this paper.